The Relationship between Non-Communicable Diseases History and Health-Related Quality of Life (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
Disaster-prone population is vulnerable for suffering non-communicable diseases (NCDs) which become risk factors for poor quality of life (QoL). The study aims at investigating the effect of history of NCDs to the QoL. QoL was measured by WHODAS. NCDs with prevalence more than 1% were involved in analysis. Those NCDs included shortness of breath, diabetes, hypertension, joint disease and stroke. Among 1,872 respondents of Riskesdas, 7.7% of them have a poor QoL, suffering hypertension (8.7%), shortness of breath (7.3%) and asthma (6.9%). Risks of poor QoL six times higher among those with a history of PTM (PORadj 5.987; 95% CI 4.210-8.514) after adjusted by age, gender, education, socioeconomic status and region of residence. Stroke gives the greatest impact with POR 25.00 (95% CI 10.406 to 60.063). We recommend that the promotion and prevention of NCDs should be integrated with both mitigation-related and community resilience activities to disasters.